Local Wisdom PAUD to Grow Student’s Soft Skills (Study Cash: Development RKH On Science Learning) - Khoiri, Ahmad (Universitas Negeri Semarang, 2016)
There are various local potentials such as garden, playground, pool, and field. They can be used as laborotories and sources of contextual learning. This research aims to implement RKH (Rencana Kegiatan Harian/ Plan Daily Activities) based on local potentials developed to improve the result of teaching and learning process and students’ soft skill as well. This reseach and development is adapted from Borg and Gall (2003) combined with Sugiyono (2010). Product validation stage results RKH which deserves to be implemented. Date gathering uses tes, questionnaire, soft skill performance, observing the communicatoin skill, teaching and learning process, and interview. This research makes some results. RKH based on local potentials gives information about pontentials in local area. In addition, it can be developed to be creative idea in order to improve the students’ capability in asking questions. Approximately 81% of the students give good respons. They are interested in RKH water and air, flood, and volcano eruption, so they understand the science easily and they are motivated to know more about science. The students’ soft skill is getting improvement. The result of learning is 0.36 better. Meanwhile, coefficient t test hypothesis related varians with thit> ttabel (t1=2,07>1,99; t2=4,17>1,99; t3=2,34>1,99; t4=5,34>1,99;) shows that RKH science based on local potentials for PAUD is well-developed effectivelly to improve the result of learning and soft skill.